What really matters: Discounting, technological change and sustainable climate - Georg Müller-Fürstenberger; Gunter Stephan (University of Bern, Department of Economics, 2010)
This paper discusses the interplay between the choice of the discount rate, greenhouse gas mitigation and endogenous technological change. Neglecting the issue of uncertainty it is shown that the green golden rule stock of atmospheric carbon is uniquely determined, but is not affected by technological change. More general it is shown analytically within the framework of a reduced model of integrated assessment that optimal stationary stocks of atmospheric carbon depend on the choice of the discount rate, but are independent of the stock of technological knowledge. These results are then reinforced numerically in a fully specified integrated assessment analysis.
Keywords: Q40; O13; 330; integrated assessment; discount rate; endogenous technological change; climate change; Treibhausgas; Umweltschutz; Klimawandel; Endogener technischer Fortschritt; Theorie